Adiponectin serum levels and ADIPOQ (rs2241766) polymorphism in alopecia areata Egyptian patients - Azza Gaber Antar Farag; Eman Abd-Elfatah Badr; Banan Mohamed Gamal Abd-Elaty; Nada Farag Elnaidany; Mai Medhat Mohamed Ghanem (Sociedade Brasileira de Dermatologia, 2024)
Abstract Background Alopecia Areata (AA) is an acquired autoimmune form of non-scarring hair loss. Adiponectin and its gene polymorphism were related to many autoimmune disorders. Objective Assessment of adiponectin serum levels and adiponectin gene (ADIPOQ) (rs2241766) Single Nucleoid Polymorphism (SNP) in AA patients and correlating the results with the disease severity in those patients. Methods This study included 75 AA patients and 75 age and gender-matched healthy subjects (controls). The severity of Alopecia Tool (SALT) score assessment to evaluate AA severity was done. Adiponectin serum levels by ELISA and ADIPOQ (rs2241766) SNP using PCR were performed. Results Adiponectin serum levels were significantly lower in AA patients than controls (p = 0.001). ADIPOQ (rs2241766) TG genotype and G allele were significantly predominant in AA patients increasing its risk by 5 and 4 folds (OR = 5.17, p = 0.001), (OR = 3.82, p = 0.001) respectively. Serum adiponectin levels were negatively correlated with SALT score (r = -0.435, p = 0.001) and associated with alopecia totalis (p = 0.016). ADIPOQ (rs2241766) TG genotype was significantly associated with low serum adiponectin levels and higher SALT score (p = 0.001). Study limitations The small sample size. Conclusions ADIPOQ (rs2241766) gene polymorphism (TG genotype and G allele) may modulate AA risk and contribute to the development of AA in Egyptian populations. Decreased circulating adiponectin levels may have a dynamic role in AA etiopathogenesis. Adiponectin serum concentration can be considered a severity marker of hair loss in AA.